Une critique de l’heuristique de la peur à usage des éducateurs contemporains - Camille Roelens (Éducation et Socialisation)
This article is based on a critical discussion on the mobilization of the vulnerability/responsibility couple in Hans Jonas’ work. The idea is to think about what can be done today in terms of responsible action when facing the vulnerability of others, more specifically in the context of education for autonomy. The discussion is conducted from the point of view of political philosophy of education. The first part summarizes Jonas' contributions and proposals on the topic of this dossier, as well as their posterities. A second part questions the authoritarian perspectives that may result from those considerations, whereas the third part examine their possible abstentionist and/or precautionary perspectives. Contrary to heuristic of fear advocated by Jonas, the conclusion of this text invites to think of a prudent and humanistic educational action, in the perspective of a teleological individualism and a substantial consideration of the contemporary challenge of human autonomy.